2007
DOI: 10.1002/jccs.200700138
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient and Selective Membrane Transport of Silver(I) Using Dibenzodiaza‐15‐Crown‐4 as a Selective Ion Carrier

Abstract: A chloroform membrane system containing dibenzodiaza-15-crown-4 was found to be a highly efficient and selective transport of Ag + ions through a chloroform liquid membrane. In the presence of thiosulfate ion as a suitable ion stripping agent in the receiving phase, the amount of silver transported across the liquid membrane after 105 min is 95 ± 1.3%. The selectivity of Ag + transport from aqueous solutions containing Tl + , Pb 2+ , Cd 2+ , Ni 2+ , Co 2+ , K + , Ca 2+ , Sr 2+ , Hg 2+ , Zn 2+ , Cu 2+ was inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…1). [4][5][6] The inner aqueous phase (source phase, SP, 5 mL) contained lead nitrate (1.0´10 -4 M). The outer aqueous phase (receiving phase, RP) included sodium thiosulfate (10 mL, 0.2 M).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). [4][5][6] The inner aqueous phase (source phase, SP, 5 mL) contained lead nitrate (1.0´10 -4 M). The outer aqueous phase (receiving phase, RP) included sodium thiosulfate (10 mL, 0.2 M).…”
Section: Methodsmentioning
confidence: 99%
“…For these reasons, liquid-membrane transport has attracted worldwide attention, and much work has been directed toward developing methods for its application to the separation of various metal ions. [2][3][4][5][6][7] Different methods for the specific transport of Pb 2+ ions across a liquid membrane have been reported which have drawbacks of a slow rate for transport or a lack of high selectivity. For example, it has been reported that, although using diionizable carrier such as acyclic polyether dicarboxylic acids in liquid membrane transport markedly reduces the effect of concomitance transport of anions from the aqueous phase, it suffers from long times require for the transport of Pb 2+ (about 2 days).…”
Section: Introductionmentioning
confidence: 99%
“…Cho et al claimed that a single transport of Cd(II) across emulsion LMs mediated by diaza-18-crown-6 (DA18C6) from 0.4 mol·L −1 SCN − aqueous solutions is much more effective in comparison with Zn(II) . On the other hand, we found the quantitative transport of Ag(I) in the presence of Zn(II), Cd(II), Pb(II), Co(II), Ni(II), Tl(I), K(I), Ca(II), Sr(II), Hg(II), and Cu(II) ions through bulk liquid membranes (BLMs) using azacrown ether …”
Section: Introductionmentioning
confidence: 99%